2021
DOI: 10.1111/tmi.13599
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in hypertension care and control: a population‐based study in low‐income urban Medellin, Colombia

Abstract: Objectives To assess hypertension prevalence and the extent and associated factors of hypertension diagnosis, follow‐up, treatment and control gaps in low‐income urban Medellin, Colombia. Methods We randomly sampled 1873 adults aged 35 or older. Unaware hypertensive individuals were defined as those without previous diagnosis whose average blood pressure was equal to or above 140/90 mmHg. For aware hypertensive patients, control was delimited as average blood pressure below 140/90 if under 59 years old or diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Our results show that patients had progressively lower systolic blood pressure and higher levels of hypertension control throughout time. This suggests that this sample had a high level of control when compared to other studies in Colombia, which reported much lower levels (7,44,45). These differences might be explained by the higher levels of adherence to the treatment found in another study with this same sample, particularly in terms of pharmacological treatment adherence (46).…”
Section: Discussionmentioning
confidence: 51%
“…Our results show that patients had progressively lower systolic blood pressure and higher levels of hypertension control throughout time. This suggests that this sample had a high level of control when compared to other studies in Colombia, which reported much lower levels (7,44,45). These differences might be explained by the higher levels of adherence to the treatment found in another study with this same sample, particularly in terms of pharmacological treatment adherence (46).…”
Section: Discussionmentioning
confidence: 51%
“…The reported prevalence of hypertension in Colombia depends on the sampled population (Table 1 ), but hypertension affects between 28 and 44% of the adult population [ 10 , 11 , 15 18 ]. The prevalence increases with age [ 17 , 19 ], body mass index (BMI) [ 16 , 17 , 20 ], comorbidities [ 21 ], and correlates of low socioeconomic status, such as low education level and Afro-descendent ethnicity [ 15 , 17 , 18 ].…”
Section: Epidemiology Of Hypertension In Colombiamentioning
confidence: 99%
“…Among Colombian patients treated for hypertension, ~ 65% achieve BP control, but because many patients do not receive treatment, this equates to BP control in only ~ 39% of patients with hypertension [ 10 , 11 ]. In the 2016 Colombian National Survey of Health, Welfare and Aging, factors associated with poor BP control were age > 74 years and living in a rural area [ 24 ].…”
Section: Issues In Hypertension Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, we conducted a cross-sectional survey in a low-income commune of Medellin 19 to estimate the prevalence of hypertension in the adult population and the magnitude and determinants of the main gaps in hypertension care and control. The definitions of those gaps are shown in table 1 .…”
Section: Introductionmentioning
confidence: 99%